Encapsulated Mesenchymal Stem Cell as Regenerative Alternative for MDR-TB: A Gene Expression Analysis of ABCG2 Efflux - Christine Verawaty Sibuea; Dina Octafrida Marpaung; Ervina Julien Sitanggang; Ade Pryta Simaremare; Cindy Destasya Masal; George Azriel Buala Nama Laia; Octora Angelica Violyn Tambunan; Wanda Lucia Samosir; Cici Kres Sidabalok (Postgraduate, University of Mataram, 2025)
Multidrug-resistant tuberculosis (MDR-TB) poses a significant global health challenge due to poor treatment outcomes. Encapsulated mesenchymal stem cells (MSCs) have emerged as a potential alternative therapy; however, their role in modulating bacterial drug sensitivity remains unclear. This study aimed to evaluate the expression of the ABCG2 efflux pump gene in encapsulated MSCs co-cultured with MDR-TB, and to explore its implications for bacterial sensitivity to anti-tuberculosis drugs. An in vitro experimental design was employed using encapsulated MSCs cultured with MDR-TB. Total RNA was isolated, converted into complementary DNA (cDNA), and analyzed using quantitative real-time PCR (RT-PCR). Gene expression levels were quantified using the Livak (ΔΔCt) method. Results demonstrated a progressive increase in ABCG2 gene expression on days 2, 7, and 14. Although this increase may reduce the direct antibacterial capacity of MSCs, previous studies have shown that their preserved paracrine function remains beneficial for immunomodulation. These findings support the continued investigation of encapsulated MSCs as an adjunctive therapy for MDR-TB, particularly through immunoregulatory mechanisms despite increased ABCG2 expression.